PENDAMPINGAN PENYUSUNAN LAPORAN KEUANGAN HIMAWARI HANDMADE PANTI ASUHAN MUHAMMADIYAH PUTRI ULIL ABSHAR - Agustin Dwi Haryanti; Thoufan Nur (Jurnal Pengabdian dan Peningkatan Mutu Masyarakat, 2020)
The service was carried out at Panti Asuhan Muhammadiyah Putri Ulil Abshar. Panti Asuhan as a partner is one of Muhammadiyah Charitable Enterprises and included in the area of Aisyiyah Leader, Jetak Lor, Dau, Malang. Mitra has a business Himawari Handmade. The business produces bags, wallets, and some household products in the handmade category. The results of the business become a source of independent funds for partner. Service’s aims help partner through financial reporting preparation assistance. Service produces a financial reporting system by Microsoft Access (Microsoft Office 2016). The system produces integrated financial reports. Thus, partners will not do the recording and reporting manually. The system provides accurate and timely accounting data and information. Partners can analyze and make financial decisions well. Service done with several steps. Service starts by identifying the business activities of partner. The next step is discuss the needs of financial statements. The sfattep continued with the design of the Miscrosoft Access financial reporting system. The design is accompanied by the preparation of a system operational work guide for partners. The last step is training for business managers financial reports. The results can improve partner’s' ability to manage finances. Partner can understand and apply the concept of financial reporting to support business activities. This is indicated by the ability of partners to prepare financial statements. In addition, partners can use financial statements as a decision-making tool for the development of the Himawari Handmade business.Keywords : financial, report, business